Lung-specific metastasis: the coevolution of tumor cells and lung microenvironment - Guixiu Xiao; Xinmin Wang; Zihan Xu; Yanyang Liu; Jing Jing (Molecular Cancer)
Abstract The vast majority of cancer-related deaths are attributed to metastasis. The lung, being a common site for cancer metastasis, is highly prone to being a target for multiple cancer types and causes a heavy disease burden. Accumulating evidence has demonstrated that tumor metastasis necessitates continuous interactions between tumor cells and distant metastatic niches. Nevertheless, a comprehensive elucidation of the underlying mechanisms governing lung-specific metastasis still poses a formidable challenge. In this review, we depict the lung susceptibility and the molecular profiles of tumors with the potential for lung metastasis. Under the conceptual framework of “Reciprocal Tumor-Lung Metastatic Symbiosis” (RTLMS), we mechanistically delineate the bidirectional regulatory dynamics and coevolutionary adaptation between tumor cells and distal pulmonary niches during lung-specific metastasis, including the induction of pre-metastatic-niches, positive responses of the lung, tumor colonization, dormancy, and reawakening. An enhanced understanding of the latest mechanisms is essential for developing targeted strategies to counteract lung-specific metastasis.